Clinical Laboratory Personnel—Is There a Shortage in California? - Puffer, Jean (1970)
In a study of vacancy rates for laboratory personnel in California to determine if there is in fact a serious or critical shortage of qualified individuals in this group of allied health professionals, it was found that while the answer is still elusive, it would appear that although the shortage may be somewhat greater than normal it is not critical in most areas of the state. For most areas, the situation seems to have improved from 1966 to 1968. There are a few geographical areas, predominantly rural, where shortages of licensed personnel are critical. Vacancy rates also are higher in hospital laboratories. Recruitment difficulties in these situations may be related to insufficient incentives, including but not necessarily limited to salaries. Training in California laboratories may facilitate recruitment in specific instances, and may assume greater importance in the future as working conditions for health professionals continue to improve in other states. And finally, the use of laboratory assistants, aides, and clerks can materially assist the laboratory work, thereby freeing the licensed professional staff to accept responsibilities commensurate with the increasing sophistication of laboratory knowledge and practice.